Impact of Political Stability and Human Capital on Foreign Direct Investment in East Asia & Pacific and South Asian Countries - Sabir, Samina; Khan, Ahsan (Asian Journal of Economic Modelling, 2018)
The objective of this study is to analyze the impact of political stability and human capital on FDI in Asian countries. To attain this objective, this study employs Panel data fixed effect and generalized method of moment techniques on a sample of 18 South Asian and East Asia and Pacific countries for the period 1981 to 2015. The results from full sample of countries show that political stability and human capital affect FDI significantly with correct signs. The region wise comparative analysis indicates that variables like; Inflation, GDP per capita and political stability have been found to have greater effects on FDI in East Asia and Pacific region while trade openness, average year of primary schooling and average year of secondary schooling are found to be more effective in case of South Asian region. The paper concludes that Asian countries should improve their macroeconomic indicator along with political stability and human capital to attract FDI in this region.